Needs Analysis of Design for the Integrated Project-Based Learning Module at Edupark Physics Science and Technology Center Sawahlunto - Adji Waskita; Hamdi Rifai (Physics Learning and Education, 2023)
Visiting a Geopark or tourist attraction has become a lifestyle of the community, but the visit is still limited to a tourist visit and the activity is no more than to capture moments or recreation such as enjoying the beauty of nature, taking pictures, selfies, playing and others. Geoparks or tourist attractions as learning resources have not been maximally utilized, including the Sawahlunto Science and Technology Center. This research is a preliminary research that aims to analyze the needs in the development of physics edupark-based learning modules at the iptek center destination in sawahlunto. The type of research used is R&D (Research and Development) or also known as research and development using the Plomp model. This research is only a preliminary research stage consisting of teacher analysis, student analysis, and analysis of potential materials at the sawahlunto science and technology center. Data used in this study were obtained from interviews and questionnaires given to physics teachers and 30 students of class XI SMAN 13 Padang. Based on this preliminary research, the results obtained that teaching materials in the form of PjBL-based modules associated with edupark have benefits to; motivate students in learning, display physics phenomena as a whole, help develop students' knowledge and skills and help students in mastering physics material. In addition, the sawahlunto science and technology center tourism activities can be used as a physics edupark and as an object for developing teaching materials in the form of PjBL-based modules in the form of photos and videos because they have a lot to do with physics concepts. So it can be concluded that the PjBL-based learning module is a suitable teaching material if used as a physics edupark learning media.